Absence of oncomodulin increases susceptibility to noise-induced outer hair cell death and alters mitochondrial morphology - Murtha, Kaitlin E.; Sese, Weintari D.; Sleiman, Kiah; Halpage, Janith; Padyala, Pravallika; Yang, Yang; Hornak, Aubrey J.; Simmons, Dwayne D. (Frontiers in Neurology, 2024)
Cochlear outer hair cells (OHCs) play a fundamental role in the hearing sensitivity and frequency selectivity of mammalian hearing and are especially vulnerable to noise-induced damage. The OHCs depend on Ca 2+ homeostasis, which is a balance between Ca 2+ influx and extrusion, as well as Ca 2+ buffering by proteins and organelles. Alterations in OHC Ca 2+ homeostasis is not only an immediate response to noise, but also associated with impaired auditory function. However, there is little known about the contribution of Ca 2+ buffering proteins and organelles to the vulnerability of OHCs to noise. In this study, we used a knockout (KO) mouse model where oncomodulin (Ocm), the major Ca 2+ binding protein preferentially expressed in OHCs, is deleted. We show that Ocm KO mice were more susceptible to noise induced hearing loss compared to wildtype (WT) mice. Following noise exposure (106 dB SPL, 2 hrs), Ocm KO mice had higher threshold shifts and increased OHC loss and TUNEL staining, compared to age-matched WT mice. Mitochondrial morphology was significantly altered in Ocm KO OHCs compared to WT OHCs. Before noise exposure, Ocm KO OHCs showed decreased mitochondrial abundance, volume, and branching compared to WT OHCs, as measured by immunocytochemical staining of outer mitochondrial membrane protein, TOM20. Following noise exposure, mitochondrial proteins were barely visible in Ocm KO OHCs. Using a mammalian cell culture model of prolonged cytosolic Ca 2+ overload, we show that OCM has protective effects against changes in mitochondrial morphology and apoptosis. These experiments suggest that disruption of Ca 2+ buffering leads to an increase in noise vulnerability and mitochondrial-associated changes in OHCs.